Longaberger : an American success story - Longaberger, Dave.; Shook, Robert L., 1938- (New York : HarperBusiness, 2001)
Longaberger describes how he used an unconventional management style to build his company into the largest basket maker in the U.S
Keywords: Longaberger, Dave; Longaberger Company -- History; Basket making -- Ohio -- History; Basket makers -- Ohio -- Biography